Recent advances in ultrafast plasmonics: from strong field physics to ultraprecision spectroscopy - Kim, San; Jeong, Tae-In; Park, Jongkyoon; Ciappina, Marcelo F; Kim, Seungchul (Nanophotonics (Berlin, Germany), 2022)
Surface plasmons, the collective oscillation of electrons, enable the manipulation of optical fields with unprecedented spatial and time resolutions. They are the workhorse of a large set of applications, such as chemical/biological sensors or Raman scattering spectroscopy, to name only a few. In particular, the ultrafast optical response configures one of the most fundamental characteristics of surface plasmons. Thus, the rich physics about photon-electron interactions could be retrieved and studied in detail. The associated plasmon-enhanced electric fields, generated by focusing the surface plasmons far beyond the diffraction limit, allow reaching the strong field regime with relatively low input laser intensities. This is in clear contrast to conventional optical methods, where their intrinsic limitations demand the use of large and costly laser amplifiers, to attain high electric fields, able to manipulate the electron dynamics in the non-linear regime. Moreover, the coherent plasmonic field excited by the optical field inherits an ultrahigh precision that could be properly exploited in, for instance, ultraprecision spectroscopy. In this review, we summarize the research achievements and developments in ultrafast plasmonics over the last decade. We particularly emphasize the strong-field physics aspects and the ultraprecision spectroscopy using optical frequency combs.
Keywords: optical frequency comb; photoelectron spectroscopy; ultrafast plasmonics; strong-field physics; surface plasmons